2009
DOI: 10.1007/s12298-009-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

High frequency plant regeneration from embryogenic callus of a popular indica rice (Oryza sativa L.)

Abstract: The aim of the study is to establish a routine procedure for high frequency plant regeneration from in vitro raised embryogenic callus of abiotic salt sensitive indica rice (Oryza sativa L.) cultivar ADT 43. The effect of synthetic auxin 2,4-D on callus induction was optimized to achieve high frequency plant regeneration from fresh embryogenic callus without further subculture. Friable, nodular and creamish-white embryogenic callus cultures were raised from mature rice seeds on LS medium supplemented with 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…Similarly, in Sambha mahsuri cultivar, maximum multiple shoots regeneration was achieved in supplementation of MS + BAP (5.0 mg L −1 ). Simultaneously, stimulatory effects of BAP in combination with IAA and NAA have previously been reported to facilitate regeneration in indica rice cell cultures (Mandal et al 2003; Karthekeyan et al 2009). The observed results revealed that kinetin was found to be effective for the induction and proliferation of shoots and roots.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, in Sambha mahsuri cultivar, maximum multiple shoots regeneration was achieved in supplementation of MS + BAP (5.0 mg L −1 ). Simultaneously, stimulatory effects of BAP in combination with IAA and NAA have previously been reported to facilitate regeneration in indica rice cell cultures (Mandal et al 2003; Karthekeyan et al 2009). The observed results revealed that kinetin was found to be effective for the induction and proliferation of shoots and roots.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, we succeeded in obtaining efficient and short-term protocol for high frequency plant regeneration from mature seed derived embryogenic calli in order to use them for genetic transformation experiments as done previously in ADT 43 (Karthikeyan et al 2009). 2,4-D at 2.5 mg/l was found to be satisfactory in inducing regenerable calli from mature seed explants.…”
Section: Discussionmentioning
confidence: 99%
“…ADT 43 is indica type rice (IET 14879), medium slender white, abiotic stress sensitive, and dwarf rice of IR 509 improved ponni parentage yielding 56 Q/ha in 110 days. High frequency plant regeneration from embryogenic callus tissues have been reported from our group in this abiotic sensitive popular indica rice variety (ADT 43) in a shorter duration using embryogenic callus cultures (Karthikeyan et al 2009). In Tamil Nadu, rice is cultivated in 1.52 million hectares of which ADT 43 alone constitutes nearly 21% (Selvaraj and Ramasamy 2006).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It cultivates on approximately 17% of the cultivatable lands and plays a key role in economic development, food security and supply, human nutrition and is an important source of calories and proteins for human [1]. While, genetic engineering of wheat provides an efficient strategy for improvement of agronomic traits such as quality and disease resistance, but the graminaceous species are recalcitrant to in vitro regeneration and manipulations [2,3]. An efficient regeneration system is the main pre-requisite for the application of genetic transformation and functional genomics studies in the primomovente of important plants [4].…”
Section: Introductionmentioning
confidence: 99%